THE RELATIONSHIP OF FINANCIAL ATTITUDE, FINANCIAL KNOWLEDGE AND FINANCIAL CAPABILITY TOWARD FINANCIAL WELL-BEING AMONG WORKERS: AN EMPIRICAL INVESTIGATION - Nor Shahrina Mohd Rafien; Shafinar Ismail (International Journal of Accounting, Finance and Business, 2021)
Financial well-being is explained where an individual can control the financial matter on current life and future life as well without feeling worries on his or her financial situation and it is vital to get better quality of life. Therefore, the aim of this study is to investigate the factors that influencing financial well-being among workers. The variables for this study consist of financial attitude, financial knowledge and financial capability. A total of 109 respondents aged between 21-40 years participated in the survey using purposive sampling technique among working persons in all states in Peninsular Malaysia. The data collected via online form. Multiple regression analysis is employed to analyse the data gathered. The findings revealed that there was an insignificant relationship between financial attitude and financial knowledge with financial well-being among workers. However, there was a significant effect between financial capability with financial well-being among workers. The results could be used as guide to related government agencies, financial institutions, and the individual as well in understanding the important of financial well-being to curb from facing financial problem and to sustain the quality of life.